The European Territorial Cooperation as the Tool for Europe’s Integration: Example of Latvia - Belarus Cross - Border Cooperation - Balodis, Janis (European Journal of Multidisciplinary Studies, 2017)
The European Territorial cooperation is important part of the EU regional policy. It examines the relationships between countries and territories. Cross border cooperation is an institutional and a political oriented cooperation between two or more administrative and sovereign units. In this paper cross border cooperation was analysed as an institutional process of interstate cooperation and cross border cooperation between administrative units in Belarus – Latvia’s borderland. European integration and cross border cooperation are linked by 1) integrated economic space across the member states by Henk van Houtum, 2) the intersection between the history of European integration and the more general research field of border studies by Birte Wassenberg and 3) more gradual process and impact on border locations after the Second World war by Steven Brakman, Harry Garretsen, Charles van Marrewijk and Abdella Oumer. The theoretical approach of cross border cooperation includes - 1) the relation between core and periphery, 2) the division of exogenous and endogenous factors and 3) types of borderlands (alienated borderlands, co – existent borderlands, interdependent borderlands and integrated borderlands). Further theorethical concepts are drivers of cross-border co – operation (economic, political leadership, identity/cultural and geographical drivers). The research question is - ‘’How cross – border cooperation can influence the integration and cooperation between Latvia and Belarus? How far cooperation with an EU neighbour takes on hegemonic traits or not? Which are the cross border cooperation forms between Belarus and Latvia which ‘’makes’’ the integration between Belarus and Latvia’’.